2008
DOI: 10.1152/ajpheart.01249.2007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase decreases β-adrenergic responsiveness via inhibition of the L-type Ca2+ current

Abstract: Wang H, Kohr MJ, Wheeler DG, Ziolo MT. Endothelial nitric oxide synthase decreases ␤-adrenergic responsiveness via inhibition of the L-type Ca 2ϩ current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
81
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 54 publications
18
81
4
1
Order By: Relevance
“…Mice lacking NOS3 display a slower heart rate, and an increase in the transient inward current that has been coupled to aminoglycoside-induced ventricular ectopy and tachycardia (182). While NOS3 -/ -myocytes have normal resting action potential duration (APD) and LTCC current under basal condition, their response to ISO is altered, with longer APD and augmented I Ca associated with increases in early and delayed afterdepolarizations (243). The latter may be related to a loss-of-negative cGMP/PKG effects on the bsubunit of the LTCC (256).…”
Section: Nos and Arrhythmiamentioning
confidence: 99%
“…Mice lacking NOS3 display a slower heart rate, and an increase in the transient inward current that has been coupled to aminoglycoside-induced ventricular ectopy and tachycardia (182). While NOS3 -/ -myocytes have normal resting action potential duration (APD) and LTCC current under basal condition, their response to ISO is altered, with longer APD and augmented I Ca associated with increases in early and delayed afterdepolarizations (243). The latter may be related to a loss-of-negative cGMP/PKG effects on the bsubunit of the LTCC (256).…”
Section: Nos and Arrhythmiamentioning
confidence: 99%
“…39 Therefore, the high nNOS levels during the animals active period when sympathetic activity is highest and subject to surges, could act to reduce the incidence of arrhythmias during periods of high stress. It remains to be seen whether diurnal variation in nNOS signaling are also present in other species, including man.…”
Section: Diurnal Variation In ␤-Adrenergic Stimulation Influences Arrmentioning
confidence: 99%
“…Although HA inhibited H295R cell proliferation by increasing InsPn levels without activating aldosterone production, it is possible that HA stimulates NOS enzyme activity (via Ca 2C ), blocking steroidogenesis as described previously for MA-10 LCs by us (Mondillo et al 2009) and has been observed in other steroidogenic systems (Ducsay & Myers 2011). Regarding this, it has been demonstrated that NOS can inhibit L-type calcium channels (Wang et al 2008), which are necessary for AII-mediated steroidogenesis. Supposing that HA induced NOS in H295R cells, the entry of calcium through the L-channels would be blocked, thus preventing aldosterone synthesis, without affecting the proliferation pathway.…”
Section: Discussionmentioning
confidence: 61%